PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATA PELAJARAN KIMIA MATERI LAJU REAKSI DI SMA NEGERI 2 TONDANO - Saenal, Muhammad; Lombok, Johny Z.; Caroles, Joice D. S (LPPM Politeknik Saint Paul Sorong, 2025)
The development of android-based learning media in chemistry subject matter of reaction rates in this study aims to determine the feasibility of the learning media that has been made. This research is a Research and Development by adapting the ADDIE development model which consists of five stages, namely Analysis, Design, Development, Implementation and Evaluation. The data collection instruments in this study consisted of material expert validation sheets and media expert validation sheets as well as educator and student response questionnaires. This study shows that the results of the media expert validation carried out obtained an average percentage of 88.3% with the appropriate or valid category and the results of the material expert validation carried out obtained an average percentage of 87.5% with the appropriate or valid category and the results questionnaires from educator responses obtained an average percentage of 98.6% in the appropriate or valid category and questionnaires from student responses obtained an average percentage of 87.4% in the appropriate or valid category. The developed learning media is able to improve student learning outcomes from an average percentage of 75.9% to 84.4%. Based on the results of the description above, the android-based chemistry learning media on the reaction rate material developed is considered feasible and effective for use in chemistry learning